The Development of English Writing Skills Using the Writing Process Approach for Fourth Grade Students - Pinichwinyupab, Parichat; Thipatdee, Goachagorn (Journal of Roi Et Rajabhat University, 2020)
The purposes of this study were to compare English writing skills of fourth grade students before and after learning using the writing process approach, and to study the effectiveness index of an activity package on English writing skills using the writing process approach. The sample was 30 students studying in grade 4 at Ban Dangmoh School, and Ban Tun School, Khueang Nai District, Ubon Ratchathani Primary Educational Service Area Office 1. The participants were selected by cluster random sampling. The research instruments were 6 learning kits to develop English writing skills by using the writing process approach, and a subjective writing skill test which contained 3 parts. The collected data were analyzed by using the statistics of percentage, mean, standard deviation, and t-test. The research findings were as follows. 1) Students’ English writing skills after using the writing process approach were statistically significantly higher than before learning at .01 level. 2) The effectiveness index of leaning kits on English writing skills using the writing process approach was .7371. This indicated that students’ writing ability was increased by 73.71 percent which met the specified criterion of .05.